Mind the perception gap: Identifying differences in views among stakeholder groups of shared mobility services through bayesian best-worst method - Ehsan Amirnazmiafshar; Marco Diana (Multimodal Transportation)
This study investigates perception gaps among stakeholders—policy-makers, operators, users, and non-users—regarding car-sharing, bike-sharing, and scooter-sharing systems in Turin, Italy. Based on 628 surveys collected between November 2021 and February 2022 and analyzed using the Bayesian Best-Worst Method (BWM) multicriteria technique, it highlights key differences in prioritizing factors influencing shared mobility demand.Key Findings: For car-sharing, policy-makers overestimate the importance of trip purpose compared to both users and non-users, while undervaluing service availability. Operators undervalue trip-related factors, such as travel time and departure time, while overemphasizing user-friendliness. For bike-sharing, policy-makers overestimate travel time compared to users while undervaluing travel comfort and environmental friendliness compared to both users and non-users. Operators underestimate trip-related factors, including travel distance and trip purpose, while overemphasizing environmental friendliness, particularly compared to non-users. For scooter-sharing, policy-makers underestimate trip-related characteristics, such as travel time and departure time, while overestimating travel cost and user-friendliness compared to non-users. Operators undervalue travel comfort and service availability, while overestimating travel distance, especially compared to users.Managerial Insights: For car-sharing, policy-makers should expand service coverage and incentivize vehicle deployment, while operators should use dynamic fleet management and offer flexible booking options. For bike-sharing, policy-makers should subsidize fleet expansion and improve infrastructure, while operators should transition to free-floating models and integrate navigation tools. For scooter-sharing, policy-makers should enforce safety standards and improve accessibility, while operators should invest in high-quality scooters and adopt competitive pricing models.Bridging these perception gaps is essential for fostering shared mobility adoption and enhancing user satisfaction.